Beyond binaries: mixed-blood Indigenous inequalities. (June 2023) - Dicks, Heather
This article explores existing research related to mixed-blood Indigenous individuals in an effort to reveal a more complete picture of social inequality that exists within and between the binary categorization of Indigenous and non-Indigenous within Canada. Tracing a line through past and present discriminatory assimilationist policies, this article reveals the pervasive challenges associated with living as a mixed-blood Indigenous person in this country. Marked by a perpetual struggle to gain recognition from both Indigenous and settler populations, individuals living within this marginal identity face a structure of inequality that is little explored in contemporary research literature.